The economics of energy and the production process : an evolutionary approach - Buenstorf, Guido (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2004)
The book attempts to break new ground in the theory of production. Turning away from the ever more abstract - and theoretically empty - production function approach, the author shows how changing physical constraints in the utilisation of energy systematically affect production processes in the economy. With his analysis the author challenges the value based approach to production. He outlines the contours of a richer theory, which is capable of accounting for physical and technological aspects without losing sight of their economic implications.
Series editor (New horizons in institutional and evolutionary economics): Geoffrey M. Hodgson.
Includes bibliographical references (p. 179-193) and index.
lje 25/08/16
Loans
Keywords: Energy policy; Economic policy; Power resources